Pendidikan Humanistik dalam Persepektif Ki Hajar Dewantara dan Implikasinya dalam Menanamkan Nilai-Nilai Budi Pekerti bagi Peserta Didik - Verina, Ika; Margarini, Yuli Dwi Bina; Nurfuadi, Nurfuadi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
This study aims to explore the implementation of humanistic education within the framework of Ki Hajar Dewantara’s Tri Center of Education theory and its implications for instilling moral values (budi pekerti) in elementary schools. Using a qualitative approach with interview, observation, and literature review techniques, this research examines the synergy between school, family, and community environments. The findings indicate that humanistic education, which focuses on the holistic development of individual potential and positive social interaction, is highly effective in shaping students’ character. The integration of moral values such as honesty, responsibility, and empathy is carried out through active learning methods, teacher role modeling, and collaboration with parents and community leaders. Despite facing challenges such as limited resources and a lack of educators’ understanding, solutions can be achieved through professional training and the improvement of school facilities. This study concludes that harmonious collaboration among the three centers of education is the key to creating an educational ecosystem that supports the development of a character-driven and competitive future generation.